Healthcare Resource Utilization and Costs Among Commercially Insured Patients With Advanced or Recurrent Endometrial Cancer Initiating First-Line Therapy in the United States - Monica Kobayashi; Jamie Garside; Joehl Nguyen (Journal of Health Economics and Outcomes Research)
**Background:** Endometrial cancer (EC) represents a substantial economic burden for patients in the United States. Patients with advanced or recurrent EC have a much poorer prognosis than patients with early-stage EC. Data on healthcare resource utilization (HCRU) and costs for patients with advanced or recurrent EC specifically are lacking.